Swimmer’s ear: how does ear canal pave its way from ‘sensitivity to septicity’? - Ballal, Venkatesh; Basavannaiah, Sphoorthi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Otitis externa is a condition that causes inflammation of the external ear canal. It is estimated that around 1 in 10 people will be affected by this condition at some point in their lives. It is relatively common in occurrence and is referred to as "swimmer’s ear" because swimming in polluted water is a common way to contract it, but it is also possible from water trapped in the ear canal after a shower, especially in a humid climate. Hence, repeated exposure to water can make the ear canal more vulnerable to inflammation and infection. The aim of the present study is to find out the aetiology of this condition and also to educate the population regarding adapting and implementing measures so as to avoid the triggers that causes this condition. Methods: 89 patients who consulted the ENT outpatient department were clinically evaluated and diagnosis was made and treated accordingly. Results: As per the study, 79% patients in the infective group superseded 21% patients in the reactive group with the predominance of 58% patients with acute cases in terms of disease course and progression. 30% patients had repeated trauma to the ear canal as the common stimulant for the infection, that led to 25% patients with otomycosis as the commonest cause for otitis externa. Conclusions: Ear canal infection ranges from simple irritation to severe inflammation and in either scenario it should not be ignored and overlooked upon.